2021
DOI: 10.31234/osf.io/s7p5t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of motor inhibition in implicit negation processing: two Go/NoGo behavioral studies

Abstract: Several studies demonstrated that the processing of explicit forms of negation recruits motor inhibitory mechanisms. However, whether this is also true for implicit negation, in which the negative meaning is implicated but not explicitly lexicalized in the sentence (e.g., “I ignore”), has never been studied before. This study aims to address this issue via two Go/NoGo experiments applied to the processing of affirmative, explicit and implicit negation sentences, which differed for the response time-windows to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, several studies using different neuro-behavioural techniques have demonstrated that the presence of negation in a hand-related negative sentence reduces the activation of the corresponding motor areas compared to its affirmative counterparts (functional Magnetic Resonance Imaging: Tettamanti et al, 2008;Tomasino et al, 2010;electroencephalography (EEG): Alemanno et al, 2012;paired-pulses Transcranial Magnetic Stimulation: Liuzza et al, 2011;Papeo et al, 2016; kinematic measures and grasp force: Aravena et al, 2012;Bartoli et al, 2013). More recently, a series of studies have been carried out to investigate whether the processing of sentence negation involves motor inhibitory mechanisms (Beltrán et al, 2018;Beltrán et al, 2019;Foroni & Semin, 2013;García-Marco et al, 2019;Liu et al, 2019Liu et al, /2020Papeo et al, 2016;de Vega et al, 2016;Montalti et al, 2021a;Montalti et al, 2021b;Vitale et al, 2022). The majority of these studies used paradigms such as the Stop Signal Task (Logan et al, 1984) and the Go/NoGo task, which have been developed to measure motor response inhibition, embedded in a sentence comprehension task.…”
Section: The Concept Of Negation Is Multidimensionalmentioning
confidence: 99%
“…Furthermore, several studies using different neuro-behavioural techniques have demonstrated that the presence of negation in a hand-related negative sentence reduces the activation of the corresponding motor areas compared to its affirmative counterparts (functional Magnetic Resonance Imaging: Tettamanti et al, 2008;Tomasino et al, 2010;electroencephalography (EEG): Alemanno et al, 2012;paired-pulses Transcranial Magnetic Stimulation: Liuzza et al, 2011;Papeo et al, 2016; kinematic measures and grasp force: Aravena et al, 2012;Bartoli et al, 2013). More recently, a series of studies have been carried out to investigate whether the processing of sentence negation involves motor inhibitory mechanisms (Beltrán et al, 2018;Beltrán et al, 2019;Foroni & Semin, 2013;García-Marco et al, 2019;Liu et al, 2019Liu et al, /2020Papeo et al, 2016;de Vega et al, 2016;Montalti et al, 2021a;Montalti et al, 2021b;Vitale et al, 2022). The majority of these studies used paradigms such as the Stop Signal Task (Logan et al, 1984) and the Go/NoGo task, which have been developed to measure motor response inhibition, embedded in a sentence comprehension task.…”
Section: The Concept Of Negation Is Multidimensionalmentioning
confidence: 99%